2023
DOI: 10.1029/2022gl102399
|View full text |Cite
|
Sign up to set email alerts
|

Confronting Solid‐State Shear Bias: Magmatic Fabric Contribution to Crustal Seismic Anisotropy

Abstract: Seismic anisotropy is controlled by aligned rock‐forming minerals, which most studies attribute to solid‐state shear with less consideration for magmatic fabric in plutonic rocks (rigid‐body rotation of crystals in the presence of melt). Our study counters this traditional solid‐state bias by evaluating contributions from fossil magmatic fabric. We collected samples from various tectonic settings, identified mineral orientations with electron backscatter diffraction and neutron diffraction, and calculated thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 79 publications
(122 reference statements)
0
5
0
Order By: Relevance
“…Another important debate is related to the question of how the NAFZ continues in the crust and lithosphere. To shed light on this issue, we investigate the depth‐variation in anisotropic parameters that may result from a change in the dominant mineralogy at different depth layers including upper, lower crust and mantle (Bernard & Behr, 2017; Frothingham et al., 2023). These microscale variations can strongly control the regional lithospheric strength and depth distribution of strain.…”
Section: Discussionmentioning
confidence: 99%
“…Another important debate is related to the question of how the NAFZ continues in the crust and lithosphere. To shed light on this issue, we investigate the depth‐variation in anisotropic parameters that may result from a change in the dominant mineralogy at different depth layers including upper, lower crust and mantle (Bernard & Behr, 2017; Frothingham et al., 2023). These microscale variations can strongly control the regional lithospheric strength and depth distribution of strain.…”
Section: Discussionmentioning
confidence: 99%
“…As should be expected, the seismic structure of volcanic ocean islands can be very complex, resulting from pre-existing boundaries, magma reservoirs, and a complex structure that may include structural (i.e., dipping interfaces or faulting) and/or intrinsic (i.e., mineral-controlled) anisotropy. These effects on RF amplitude and arrivals are covered extensively in multiple studies (Frothingham et al, 2023;Schulte-Pelkum & Mahan, 2014;Schulte-Pelkum et al, 2020). This complexity can be observed at station HV.…”
Section: Receiver Functionsmentioning
confidence: 99%
“…This suggests that the lower crustal layer exhibits a higher Vp/Vs ratio, which implies the presence of mafic restite generated during a magma underplating process is a more plausible explanation (Figure 8). Additionally, during magma underplating processes, the alignment of minerals like amphibolite can induce moderate to strong (3%-9%) anisotropy (Frothingham et al, 2023), which has been observed at various volcanic regions (Schulte-Pelkum et al, 2020;. To further investigate the anisotropic properties of the lower crustal layer, we conducted an analysis by calculating an azimuthal contrast stack by computing the difference between southern and northern azimuth arrivals to highlight its anisotropic characteristic (Figure S9 in Supporting Information S1).…”
Section: Nature Of the Double Moho Structure Beneath The East Junggarmentioning
confidence: 99%